On Giorgos Katsambekis and Alexandros Kioupkiolis (eds.), Radical Democracy and Collective Movements Today: The Biopolitics of the Multitude Versus the Hegemony of the People - Kochkina, Maria (Stasis, 2016)
Book review:Giorgos Katsambekis and Alexandros Kioupkiolis (eds.), Radical Democracy and Collective Movements Today: The Biopolitics of the Multitude Versus the Hegemony of the PeopleFarnham: Ashgate, 2014, 247pp., ISBN 978-1409470526